Wartime Enlargement: How the War in Ukraine Transforms the Development of EU - Oleksiy Kandyuk (Athena)
The war in Ukraine has profoundly transformed the European Union’s enlargement policies, signalling a shift from economic-driven integration to a geopolitically motivated approach. Ukraine’s pursuit of EU membership during wartime highlights the interplay between strategic security imperatives and the longstanding principle of conditionality. This process not only reflects the EU’s adaptability to external pressures but also tests its ability to balance integration with the preservation of internal cohesion. The study explores how the conflict has acted as a catalyst for unprecedented consolidation among EU Member States, fostering unity on foreign policy while exposing institutional limits. The unique challenges of wartime accession underscore the need for new governance models and innovative strategies to maintain the EU’s normative and regulatory influence. As Ukraine’s integration unfolds, the findings illuminate broader implications for the EU’s transformative potential amidst shifting geopolitical landscapes.